2013
DOI: 10.1016/j.jtcvs.2012.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer lymph node micrometastasis detection using real-time polymerase chain reaction: Correlation with vascular endothelial growth factor expression

Abstract: Objectives Lymph node (LN) staging provides critical information in non-small cell lung cancer (NSCLC) patients. Lymphangiogenesis may be an important contributor to the pathophysiology of lymphatic metastases. We hypothesized that the presence of lymph node micrometastases positively correlates with VEGF-A/C/D and VEGF-receptor-3 (lymphangiogenic factors) expression in lymph nodes. Methods Forty NSCLC patients had pre-operative PET-CT and mediastinoscopy. RT-PCR assays for mRNA expression of epithelial mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…Several reports have shown that the use of immunohistochemistry (IHC) analysis significantly increases the detection rate of occult micrometastases (7). Molecular techniques as polymerase chain reaction (PCR) for p53 and K-ras and reverse transcriptase polymerase chain reaction for CEA, MUC1, CK7, CK19, VEGF and other targets have also been used (3,7,(13)(14)(15). Verhagen et al re-assessed the lymph nodes of patients who had had tumor recurrence after surgery and observed a higher prevalence of micrometastases when using serial node sectioning and immunohistochemistry (16).…”
Section: Commentarymentioning
confidence: 99%
“…Several reports have shown that the use of immunohistochemistry (IHC) analysis significantly increases the detection rate of occult micrometastases (7). Molecular techniques as polymerase chain reaction (PCR) for p53 and K-ras and reverse transcriptase polymerase chain reaction for CEA, MUC1, CK7, CK19, VEGF and other targets have also been used (3,7,(13)(14)(15). Verhagen et al re-assessed the lymph nodes of patients who had had tumor recurrence after surgery and observed a higher prevalence of micrometastases when using serial node sectioning and immunohistochemistry (16).…”
Section: Commentarymentioning
confidence: 99%
“…Особенности ангиогенеза в регио-нарных лимфатических узлах (РЛУ) у больных РЖ изуче-ны недостаточно. Данные об особенностях ангиогенеза в основном касаются изучения экспрессии VEGF в ткани РЛУ [13,15,17]. При злокачественных новообразованиях ряд авторов наблюдали реактивные изменения со сто-роны РЛУ.…”
Section: Discussionunclassified
“…У пациентов с немелкоклеточным раком легко-го прослеживалась корреляция с наличием метастазов в РЛУ, экспрессией VEGF и рецепторов к нему (VEGF-ре-цептор-3) [15].…”
Section: Discussionunclassified
“…Accurate staging is therefore extremely important and can lead to either a more extensive primary therapy to reduce the risk of local recurrence or to systemic adjuvant therapy that eliminates these occult deposits. Conventional HE staining can accurately detect gross nodal metastases in patients with NSCLC, but cannot detect LN micrometastasis (Nwogu et al, 2013). Sensitive immu-nocytochemical tests have been widely used to identify micrometastasis.…”
Section: Discussionmentioning
confidence: 99%